The Effect of Emergency Training on Improving Knowledge and Skills in Emergency Management Among Students at MAN 2 Palu - Hasnidar; Sukrang; Fauzan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: An emergency is a situation or condition where there is an immediate threat or occurrence of harm that may lead to further damage (loses). In modern times, emergency preparedness has become a critical aspect of daily life, particularly in school environments. Incidents such as accidents, fires, and the need for first aid interventions highlight the increasing importance of emergency training for students. Objective: To analyze the effect of emergency training on improving students' knowledge and skills in managing emergencies. Method: This study employed a pre-experimental design with a one-group pretest-posttest approach. A total of 81 students from MAN 2 Palu participated in the study. The Wilcoxon signed-rank test was used to assess changes in knowledge and skills, with a significance level set at p < 0.05. Result:. The mean pretest knowledge score was 9.16 (SD: 1.94), and the posttest score was 17.54 (SD: 0.67). The Wilcoxon test indicated a significant improvement in knowledge following the training (p = 0.000, p < 0.05). Similarly, the mean pretest score for basic life support skills was 3.44 (SD: 0.63), which increased to 5.93 (SD: 0.26) post-training. The mean score for splint dressing skills improved from 2.37 (SD: 0.64) pretest to 7.93 (SD: 0.30) posttest, and choking aid skills improved from 2.69 (SD: 0.54) to 3.98 (SD: 0.15) posttest. All skill improvements were statistically significant (p = 0.000, p < 0.05), which means providing emergency training has a positive effect on improving emergency skills among students. Conclusion: Emergency training significantly improves both the knowledge and skills of students in managing emergencies. This training is expected to improve students' ability to provide effective first aid in emergencies before professional medical assistance is available.